Stereocomplex Poly(Lactic Acid) Amphiphilic Conetwork Gel with Temperature and pH Dual Sensitivity - Wu, Jie (Polymers (Basel), 2019)
A novel stereocomplex poly(lactic acid) amphiphilic conetwork gel with temperature and pH dual sensitivity was synthesized by ring-opening polymerization (ROP) and free radical copolymerization. The chemical structure and composition of hydrogel were characterized by Fourier transform infrared spectroscopy (FT-IR), proton nuclear magnetic resonance ((1)H NMR) and X-ray diffraction (XRD). The temperature and pH sensitivity and good amphiphilicity of hydrogel were studied using digital photos, the swelling ratios and a scanning electron microscope (SEM). The thermal stability and mechanical properties of hydrogel were studied by differential scanning calorimeter (DSC) and dynamic viscoelastic spectrometer. The results indicated that the hydrogel has amphiphilicity, temperature and pH sensitivity, good thermal stability and mechanical strength.